Thermally Triggered Mechanically Destructive Electronics Based On Electrospun Poly(ε-caprolactone) Nanofibrous Polymer Films - Yang Gao (Nature Portfolio, 2017)
Abstract Electronics, which functions for a designed time period and then degrades or destructs, holds promise in medical implants, reconfigurable electronic devices and/or temporary functional systems. Here we report a thermally triggered mechanically destructive device, which is constructed with an ultra-thin electronic components supported by an electrospun poly(ε-caprolactone) nanofibrous polymer substrate. Upon heated over the melting temperature of the polymer, the pores of the nanofibers collapse due to the nanofibers’ microscopic polymer chain relaxing and packing. As a result, the polymer substrate exhibits approximately 97.5% area reduction. Ultra-thin electronic components can therefore be destructed concurrently. Furthermore, by integrating a thin resistive heater as the thermal trigger of Joule heating, the device is able to on-demand destruct. The experiment and analytical results illustrate the essential aspects and theoretical understanding for the thermally triggered mechanical destructive devices. The strategy suggests a viable route for designing destructive electronics.